Relationship between Plasma Level of Beta-amyloid, Alpha-synuclein, and Tau Protein with Cognitive Impairment in Parkinson Disease - Syafrita, Yuliarni; Istarini, Attiya; Busra, Meldayeni; Indra, Syarif; Susanti, Restu (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Most people with Parkinson’s disease will develop dementia along with their illness development. There are several overlapping brain pathological features in patients with Parkinson’s and Alzheimer’s disease. These features are related with beta-amyloid findings, alpha-synuclein and tau protein. Aim: This study was designed to determine the relationship between beta-amyloid, alpha-synuclein and tau protein plasma level with cognitive impairment in Parkinson’s disease. Materials and Methods: This was an observational with case-control design study. Total of 62 patients with Parkinson’s disease and 20 healthy controls were included in this study. Parkinson’s disease group was divided into 2 subgroups, patient with and without cognitive impairment based on Montreal Cognitive Assessment Indonesian version (MoCA-Ina) score. The plasma levels of beta-amyloid, alpha-synuclein, and tau protein were measured by using enzyme-linked immunoassay technique. Student’s t-test was used to analyze normally distributed data of plasma level differences between groups (Parkinson’s disease group; control group) and subgroups (Parkinson disease with and without cognitive impairment). If the data was not normally distributed, we used Mann-Whitney test. The level of significancy was <0.05 (p value <0.05). Results: The result demonstrated significant differences in beta-amyloid, alpha-synuclein, and tau protein plasma level between Parkinson’s disease and control group (p<0.05). We also found significant differences of beta-amyloid plasma level between Parkinson’s with and without cognitive impairment subgroups (p<0.05), but none in other parameters (p>0.05). Conclusion: Low plasma levels of beta-amyloid 42 (Aβ42) are associated with cognitive impairment in patients with Parkinson’s disease.